Fun with formal methods is more than fun - Shilov, N. V. (Nazarbayev University, 2014)
Almost half of a century has passed since Robert W. Floyd published the first research that explicitly discussed formally how to assign meaning to programs. But recently David L. Parnas have called Really Rethinking "Formal Methods", to question the assumptions underlying the well-known current formal software development methods to see why they have not been widely adopted and what should be changed. So, things are right where they started decades ago? Not at all, since industrial applications of Formal Methods are not the unique measure of success. Another dimension where we can discuss utility of Formal Methods could be better education. A very popular (in Russia) aphorism of Mikhail Lomonosov (the first Russian academician) says: "Mathematics should be learned just because it disciplines and bring up the mind". Similarly, Formal Methods discipline and bring up minds in Computer Science. and help to bridge a "cultural gap" (E.W.Dijkstra) between Mathematics and Computer Science.
Keywords: formal methods; method